HOUSING FINANCE: IMPACT OF HEAVY INTEREST INCOME TAX - Semenenko, Igor; Yoo, Jun Wook (International Journal of Accounting & Finance Review, 2021)
Heavy taxation of interest income becomes a structural driver of property prices in a low-interest-rate environment. Inflation-adjusted price appreciation in 1996-2017 is approximately 200 basis points higher in 14 countries allowing no exemptions on interest income than in 37 countries that tax interest income at favorable rates or provide exemptions. Results for average returns over long-term periods are confirmed in models with annual frequencies, city-level data, and in a sample of 39 OECD countries for which price/rent ratios are available. It appears that investors view direct real estate, a heavily tax-favored asset, as an inflation hedge and/or alternative to fixed income asset. Higher interest income taxation may be fueling demand for direct real estate investments by retail investors. Separately, my empirical findings suggest that easy monetary policy effects can be magnified through the housing channel in countries that do not allow exemptions on interest income. Consequently, we should expect larger investment misallocations due to asset prices departure from fundamentals in some geographies. JEL Classification Codes: E3, E4, F3, G1, G5, H2.